Розробка технології виготовлення виливка корпус Н105 методом лиття в піщано-глинисту форму - Прокоф’єв, Сергій Олександрович; Prokofiev, Serhii (ЦНТУ, 2024)
Вибрано в якості матеріалу для виготовлення виливків сплав СЧ200, описано хімічний склад, механічні та ливарні властивості сплаву. Для плавки сплаву вибрано індукційну тигельну піч типу ІЛТ-2,5 з кислою футеровкою ємністю 2500 кг. Описано принцип роботи печі. Виконано розрахунок шихти методом підбору. Для виготовлення відливків вибрано автоматичну ливарну лінію ІЛ 225 Івано-Франківського заводу „Авто-Літмаш”. Описано будову, принцип роботи та технічні характеристики лінії. Вибрано стержневий автомат для виготовлення стержнів. Вибрано матеріали та обладнання для приготування формувальних та стержневих сумішей. Описано роботу очисного відділення. Виконано аналіз конструкції деталі та технічних умов на виливок, розроблені модельно-ливарні вказівки та технічні умови на виливок, розроблено і сконструйовано ливниково-живильну систему, описано технологічний процес виготовлення виливка, описано процес проектування ливарної оснастки. Розглянуто питання техніки безпеки при литті. Розроблені технологічні креслення деталі з розробкою модельно-ливарних вказівок та форми в зборі. The material chosen for the manufacture of castings is the SC200 alloy, and the chemical composition, mechanical and casting properties of the alloy are described. An induction crucible furnace of the ILT-2.5 type with an acid lining with a capacity of 2500 kg was selected for melting the alloy. The principle of operation of the furnace is described. The charge is calculated by the method of selection. The automatic casting line IL 225 of the Ivano-Frankivsk plant "Auto-Litmash" was chosen for the production of castings. The structure, principle of operation, and technical characteristics of the line are described. A rod automatic machine for the manufacture of rods is selected. Materials and equipment for the preparation of molding and core mixtures are selected. The work of the cleaning department is described. The analysis of the part design and technical specifications for the casting is performed, model foundry instructions and technical specifications for the casting are developed, the casting and feeding system is developed and constructed, the technological process of casting manufacturing is described, the process of designing casting tooling is described. Safety issues in casting are considered. The technological drawings of the part with the development of modeling and casting instructions and the mold assembly are developed.
Development of the technology for manufacturing the casting of the H105 housing by casting in a sand-clay mold
Keywords: сірий чавун; шихта; виливок; модельно-ливарні вказівки; gray cast iron; charge; casting; modeling and casting instructions